Protecting the most vulnerable: The urgent need to include HIV-exposed children in malaria chemoprevention strategies. - Raquel González; Tacilta Nhampossa; Antía Figueroa-Romero; André-Marie Tchouatieu; Christine Manyando; Clara Menendez (PLoS Medicine)
Raquel González and colleagues discuss the drugs available to HIV-exposed children to prevent malaria infection and the urgent need to evaluate alternative agents.